Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Dinas Penanaman Modal Dan Pelayanan Perizinan Terpadu Satu Pintu Kota Sibolga - Rahmadani Rahmadani (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of Workload and Work Environment on Employee Performance at the Investment and One-Stop Integrated Service Office of Sibolga City. This research employed a quantitative approach using multiple linear regression analysis. The population consisted of 38 employees, and since the population was fewer than 100 individuals, all members were selected as the sample (census sampling). The results showed that partially, Workload has a positive and significant effect on Employee Performance, with a t-value of 3.907 > t-table 2.030 and a significance value of 0.000 < 0.05. The Work Environment also has a positive and significant effect on Employee Performance, with a t-value of 2.064 > t-table 2.030 and a significance value of 0.047 < 0.05. Simultaneously, Workload and Work Environment significantly affect Employee Performance, as indicated by an F-value of 11.073 > F-table 3.267 and a significance value of 0.000 < 0.05. The multiple linear regression equation obtained is Y = 13.369 + 0.451X1 + 0.227X2. The coefficient of determination (Adjusted R Square) of 0.388 indicates that 38.8% of the variation in Employee Performance can be explained by Workload and Work Environment, while the remaining 61.2% is influenced by other variables not examined in this study. Therefore, it can be concluded that Workload and Work Environment have a positive and significant effect on Employee Performance.